Dynamic Changes in AQP4-IgG Level and Immunological Markers During Protein-A Immunoadsorption Therapy for NMOSD: A Case Report and Literature Review - Chen, Bo; Qin, Chuan; Chen, Man; Yu, Hai-Han; Tao, Ran; Chu, Yun-Hui; Bu, Bi-Tao; Tian, Dai-Shi (Frontiers in Immunology, 2021)
The changes in the serum levels of aquaporin-4-IgG (AQP4-IgG), immunoglobulins, and inflammatory mediators in neuromyelitis optica spectrum disorder (NMOSD) cases treated with immunoadsorption have been rarely described in detail. Here we report a 29-year-old steroid-resistant NMOSD female with a severe disability (bilateral blindness and paraplegia) who received protein-A immunoadsorption as a rescue treatment. During the total 5 sessions, the circulating level of AQP4-IgG, immunoglobulins, and complement proteins (C3 and C4) showed a rapid and sawtooth-like decrease, and the serum AQP4-IgG titer declined from 1:320 to below the detectable limit at the end of the 3rd procedure. Of all the antibodies, IgG had the biggest removal rate (>96.1%), followed by IgM (>66.7%) and IgA (53%), while complement C3 and C4 also dropped by 73% and 65%, respectively. The reduced pro-inflammatory cytokines (interleukin-8 and tumor necrosis factor-α) and marked increased lymphocyte (T and B cell) counts were also observed. The improvement of symptoms initiated after the last session, with a low AQP4-IgG titer (1:32) persisting thereafter. Accordingly, protein-A immunoadsorption treatment could be one of the potential rescue therapies for steroid-resistant NMOSD patients with a severe disability.